The Transformative Role of Artificial Intelligence in Modern Education - Hasanain Mohammed Manji Al-Rzoky; Shuruq Khalid Abdulredha (Teknika, 2025)
The Fourth Industrial Revolution has led to significant advances in digital devices and social media, contributing to the emergence of artificial intelligence (AI) as a key tool for improving the educational process. Computing and information technologies have enabled the use of computers in education, particularly in computer-assisted instruction and improving classroom interaction. Artificial intelligence in education (AIEd) aims to support teaching strategies, enhance student learning, and improve educational outcomes through performance monitoring, adaptive learning, providing educational resource recommendations, and identifying educational gaps. The study focuses on exploring the role of AI applications in improving the quality of learning, assuming that these applications contribute to developing the educational process, addressing traditional challenges, and improving the performance of teachers and students. The study adopted a descriptive-analytical approach and collected data through a survey of academics and teachers in Iraq during the 2024-2025 academic year. The study recommends holding training workshops, providing necessary resources, promoting the effective use of AI applications, and developing future development plans, while proposing additional research on innovation and interactive lesson design.